Инновационные технологии личностно-ориентированного обучения в системе высшего профессионального образования - Клименко, И.С. (My University, 2016)
The article discusses the feasibility of innovative technologies in the system of student-centered learning. A brief description of how the game of social simulation, the expediency of their use in higher education. An example of using one of the methods in the educational process.
Keywords: innovative technology; social gaming simulations; student-centered approach; integration techniques